Pengembangan Sistem Penjualan Menggunakan UML dan Proses Bisnis E-Commerce Pada TB.Purnama Banjarnegara - Memi Dwi Kartika; Yudi Priyadi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
E-commerce is the result of information and communication technology that helps companies and consumers exchange information. However, there are still many companies in Indonesia that have not used e-commerce in their business activities, one of which is TB.Purnama. This company has weaknesses in the current business model, namely: the sales process is carried out conventionally, promotion through word-of-mouth, lack of attention to stock management, and limited marketing reach. This study aims to make a business model improvement plan based on the SWOT analysis results to create a building material sales prototype, which is designed using UML modeling. This modeling produces a Use Case Diagram with a series of the same number. It is consistent with 12 diagrams in Use Case Scenarios, Activity Diagrams, and Sequence Diagrams, including Payment Confirmation, Payment Verification, and Sales Data Recap. Besides, this UML also produces a Class Diagram called TB. Purnama E-Commerce System which consists of 7 classes, including Consumers, Products, and Payments. The validity and reliability test results of this floating system use Gwet's AC1 calculation, with a value of 0.75125, which is included in the type of agreement proportion "substantial." The proportion of the agreement shows that the recommendations for improving the business model and the prototype for the website user interface are good so that the recommended business model can be applied to its business activities.